Psychometric investigation of the Attention to Body Shape Scale in Brazilian adults - Teixeira, Patrícia Angélica [UNESP]; Silva, Wanderson Roberto da [UNESP]; Campos, Lucas Arrais de [UNESP]; Marôco, João; Campos, Juliana Alvares Duarte Bonini [UNESP] (FapUNIFESP (SciELO), 2022)
The objectives of the study were to develop a Portuguese version of Attention to Body Shape Scale (ABS), estimate the psychometric properties of the ABS for Brazilian data, and compare the ABS scores between the sexes and the different sample characteristics. The Portuguese version was developed following a standardized protocol. The factorial and convergent validity were evaluated using goodness-of-fit parameters and average variance extracted. Composite reliability and ordinal coefficient alpha were calculated. The invariance of the fitted model was investigated across independent subsamples using multigroup analysis. The scores were compared between variables using two-way ANOVA. A total of 1,056 individuals (71% female) with a mean age of 26.1 (SD=6.4) years participated in the study. Item 3 was removed due to low factor loading. The refined model presented good psychometric properties for the data. Different characteristics contributed to greater attention to body shape. The Portuguese version of the ABS will be useful to investigate attention to body shape in Brazil. The validity and reliability of the data supported the adequacy of the refined model. Specific characteristics influenced attention to body shape, and therefore, should be considered in future protocols.
Investigação Psicométrica da Escala de Atenção à Forma Corporal em adultos brasileiros
Keywords: Attention; Body image; Psychometry; Scale; Validation study